Catalytic enantioselective synthesis of heterobiaryl atropisomers - Surgenor, R (2021)
Heterobiaryl atropisomers comprise a privileged class of compounds whose applications span the fields of medicinal chemistry, asymmetric catalysis and materials science. In particular, axially chiral indoles have recently emerged as an important member of the atropisomeric heterobiaryl family. This thesis comprises two research projects. Initially, we describe our efforts towards an atropselective Fischer indolisation from acyclic phenylhydrazones; this highlights the challenges associated with forging a heterobiaryl axis with a sufficiently high rotational barrier. Secondly, we disclose a cheap and abundant iron catalyst (FeCl3·6H2O) that facilitates oxidative cross-coupling between 2-naphthols and C-2 substituted indoles in the presence of a chiral C2 symmetric PyBOX ligand. This reaction creates the desired aryl-aryl linkage from two C–H bonds, yielding atropisomeric heterobiaryls with excellent levels of enantioselectivity, in enantiomeric ratios of up to 98:2. The reaction also exhibits remarkable chemoselectivity, yielding exclusively the cross-coupled products without competing homocoupling of the naphthol or indole fragments. Mechanistic investigations enabled us to propose that the reaction proceeds through highly selective oxidation of the heterocycle by the Fe(III)-PyBOX complex, generating an indolyl radical. This species is then trapped by a chiral Fe(III)-bound naphtholate via a radical–anion type cross coupling process. In due course, we envision that this simple, cheap and sustainable catalytic manifold will facilitate access to a range of heterobiaryl compounds and enable their applications across a variety of fields.